Oxometal hybrid materials for oxidative desulfurization technology - Julião, Diana Cristina dos Santos Neto (2019)
Crude oil contains four classes of compounds: aromatics, cycloalkanes, alkanes and compounds with atoms of sulfur, nitrogen and/or oxygen. The presence of sulfur brings a lot of damage, for the petroleum industry itself as well as for the environment, where is a major contributor of air pollution. The EU has imposed strict legislations on the S content in transportation fuels. However, the production of such ultra-low sulfur fuels by conventional hydrodesulfurization technologies is very costly, due to the harsh conditions (high temperatures and high H2 pressures) needed that are incompatible with other important fuel requirements. The development of alternative technologies that could successfully remove sulfur under sustainable and inexpensive conditions is very important. Oxidative desulfurization (ODS) has proven to be an effective approach for this purpose. In this process the sulfur compounds are oxidized by the combination of a suitable catalyst with an oxidant. The oxidized species are removed by extraction with appropriate polar solvents. Following this strategy, in the present work novel catalytic systems were developed based on the unexplored combination Mo(VI)-oxo/H2O2 for efficiently desulfurizing model and real liquid fuels. Special attention was given to the experimental conditions, particularly the substitution of organic volatile solvents by more sustainable options, such as ionic liquids (ILs), deep-eutectic solvents (DES) or solvent-free systems. Also, low H2O2/S ratios and low temperatures (50 or 70 °C) were considered to achieve the optimal conditions. Directly or indirectly (when dissolved) all the catalysts were reused and/or recycled for several ODS cycles. In general, the desulfurization efficiency was maintained at least until the third consecutive cycle. Of all the catalysts studied, the species {PO4[MoO(O2)2]4}3- stood out due to its remarkably recyclability and stability performance for desulfurization of a model diesel for ten consecutive cycles under eco-sustainable conditions (H2O2/S = 3.7 and solvent-free system), with its immiscibility in the reaction environment being of added value. The complex IndMo(CO)3Me also displayed a remarkable behaviour under similar conditions. Both catalysts were treated as heterogeneous catalysts and recovered and reused without further treatment. Despite these outstanding results, the absence of solvent during the ODS was detrimental to the treatment of real diesel samples (2300 ppm S). The highest and the best ODS results were achieved using biphasic systems (diesel/[BMIM]PF6): IndMo(CO)3Me (95 ppm), [MoO2Cl2(DEO)] (129 ppm), CpMo(CO)3Me (372 ppm), [MoO2Cl2(DMB)2] (381 ppm), {PO4[MoO(O2)2]4}3- (500 ppm), [MoO2Cl2(di-tBu-bipy)] (621 ppm) and two hybrid molybdenum compounds (740 and 741 ppm). The species {PO4[WO(O2)2]4}3- also displayed high catalytic efficiency but using MeCN as reaction medium.